2021
DOI: 10.1016/j.econmod.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Does corruption matter for stock markets? The role of heterogeneous institutions

Abstract: In examining the role of institutions in resisting corruption and its impact on growth, most studies concentrate on the aggregate level and conclude that sound institutions enhance growth. We focus instead on varying dimensions of heterogeneous institutions in the presence of corruption and their interactive effect on stock returns in four emerging economies: Brazil, Russia, India, and China (BRIC). We pay particular attention to democratic accountability, bureaucratic quality, and law and order. Using monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 82 publications
(104 reference statements)
0
15
2
Order By: Relevance
“…Thus, demonstrate the government's ability to eloquently and politically influence policies and conventions that promote the private sector, property rights protection, improved contract enforcement, strong rule of law, and institutional justice (Hope Sr, 2020). By contrast, when institutions are weak, private sector support is ineffective, leading to bureaucracy, corruption and weak environmental regulation (Bawole & Langnel, 2021;Lakshmi et al, 2021).…”
Section: Effects Of Institutional Quality On Economic Growth and Envi...mentioning
confidence: 99%
“…Thus, demonstrate the government's ability to eloquently and politically influence policies and conventions that promote the private sector, property rights protection, improved contract enforcement, strong rule of law, and institutional justice (Hope Sr, 2020). By contrast, when institutions are weak, private sector support is ineffective, leading to bureaucracy, corruption and weak environmental regulation (Bawole & Langnel, 2021;Lakshmi et al, 2021).…”
Section: Effects Of Institutional Quality On Economic Growth and Envi...mentioning
confidence: 99%
“…The discussion indicates bi-directional causality between explanatory variables in case of Pakistan. The latest studies that support and wet this discussion include (Husnain et al, 2020;Lakshmi et al, 2021;Ouedraogo & Sawadogo, 2020;Uzum et al, 2021).…”
Section: Table 2: Descriptive Statistics For Governance Indicators An...mentioning
confidence: 91%
“…Investors are looking more at the transparency and consistency of equity markets with quality corporate management policies (D. Dang et al, 2019;Sohail et al, 2017). In a financial era of modern times, firms are not operating in a vacuum but are instead influenced by their host ecosystem governance structures that is directly influenced by voice and accountability mechanisms (Kinsella, Mehrbani, Weiser, & Weiner, 2020;Lakshmi et al, 2021;Modugu & Dempere, 2020;Montes, Bastos, & de Oliveira, 2019;Shaohua et al, 2021). Different reports have investigated the impact of V&A on stock market growth of grease-induced systemic vulnerability.…”
Section: Voice and Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The author of [35] concluded that corruption has no effect on FDI. The authors of [36] studied the impact of protectionism of property rights on the behavior pattern of multinational companies, and found that institutional performance was strongly correlated with the FDI ratio to total domestic investment. The property right importance for FDI attraction has been confirmed by the study of [37].…”
Section: Literature Reviewmentioning
confidence: 99%